2012
DOI: 10.5539/jsd.v5n11p103
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Comparative Advantage and Intra-North American Free Trade Agreement (NAFTA) Trade Performance

Abstract: The authors analysed comparative advantage of Canada, Mexico and the United States in the context of the North American Free Trade Agreement (NAFTA). The authors found that there is empirical evidence as expected that the United States of America has a large number of products in which it has a comparative advantage in, followed by Canada. Mexico is the least competitive with fewer products compared to the United States of America and Canada. The authors have also concluded that having comparative advantage is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…According to Khatibi (2008), the Ricardian theorem attributes comparative advantage to arise from the differences amongst countries based on factor scarcity. According to Mzumara et al (2012), this is not a correct position. Mzumara (2006) explains that factor endowment determines comparative advantage.…”
Section: Comparative Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…According to Khatibi (2008), the Ricardian theorem attributes comparative advantage to arise from the differences amongst countries based on factor scarcity. According to Mzumara et al (2012), this is not a correct position. Mzumara (2006) explains that factor endowment determines comparative advantage.…”
Section: Comparative Advantagementioning
confidence: 99%
“…South Africa also surpasses Mexico. Mexico has comparative advantage in 749 product lines while South Africa has comparative advantage in 824 product lines in which it has comparative advantage (Mzumara et al, 2012). South Africa also surpasses Egypt.…”
Section: Source: Computed Using Data From Trade Map (2013)mentioning
confidence: 99%
“…They also examined that favorable political conditions positively affected Athletics. Mzumara et al (2012) calculated RCA for Southern African Development Community (SADC), using HS six-digit level export data of individual member states and world export data for 2010. The RCA index indicated that SADC member states had revealed comparative advantage in mixed products, including primary and some manufactured products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the trade-related literature, there is widespread agreement that intra-SAFTA trade is not impressive (Akhter & Ghani, 2010; Akram et al, 2014; Jain & Kumar, 2018; Pushia & Jayesh, 2016; Raihan, 2012; Singh et al, 2018). This is especially observed in comparisons with other trade blocs of the world such as NAFTA, the North American Free Trade Agreement (Mzumara et al, 2012), the Asia-Pacific Economic Cooperation (APEC, 2017, 2018), ASEAN and CIS, the Commonwealth of Independent States (Basher, 2014; Karim, 2019; Kumar & Singh, 2009; Singla, 2016).…”
Section: Introductionmentioning
confidence: 97%